Repurposing FDA-approved drugs against the Crimean-Congo haemorrhagic fever virus: an in silico study - Hashim, Hayder Obayes; Omran, Aseel Mohammad; Makki Al-Hindy, Hayder Abdul-Amir; Abdulkareem, Yousif Sajjad Hasan; Jafaar Abd, Zahraa Sadeq; Rebat, Esraa Abbas; Hadi, Ruqaiya Kazem (Pharmakeftiki, 2025)
The Crimean-Congo haemorrhagic fever (CCHF) is a severe viral illness with a case fatality rate of up to 30%, typically transmitted to humans through bites from infected soft ticks. In the absence of US Food and Drug Administration (FDA)-approved antiviral therapies, novel therapeutic strategies are urgently required. This study has employed an in silico drug repurposing approach targeting the ovarian tumor domain (OTU) protease of the Crimean-Congo haemorrhagic fever virus (CCHFV), by utilizing FDA-approved pharmacological agents. A total of 1,379 compounds were virtually screened via molecular docking and molecular dynamics (MD) simulations in order to assess their binding affinities and structural stabilities. Paromomycin exhibited the strongest binding profile, with an extra precision Glide score (XP GScore) of -11.156 kcal/mol and a root mean square deviation (RMSD) consistently below 5 Å over the 50-nsec MD trajectory. Mapping against the enzymatic region of the CCHFV OTU protease has revealed multiple interactions with key catalytic residues, thereby suggesting that paromomycin may act as a reversible inhibitor of this viral protease. These findings support the hypothesis that computational techniques can identify promising candidates for CCHF treatment and underscore the need for further experimental validation of these predictions.